(untitled) (Journal of the Management Sciences, 2024)
The study was conducted to determine if electronic taxation system adopted in Nigeria was able to eliminate tax evasion and related problems associated with the manual taxation system previously in use and subsequently improving revenue generation of the government particularly company income tax and personal income tax. Primary data was obtained by means of a 5-point Likert scale questionnaire deployed to assess respondents’ perceptions and opinions related to the study’s objectives. The study deployed Kolmogorov-Smirnov test for analysis of data so obtained for the study. Result showed that (1) electronic tax system has significantly reduced tax fraud in Anambra state, Nigeria (2) electronic tax system has significantly improved revenue generation with regards to personal income tax in Anambra state, Nigeria (3) electronic tax system has significantly improved revenue generation through company income tax in Anambra state, Nigeria. With regards to the findings stated above, the study recommended that tax authorities in every state in Nigeria and other developing countries should invest in the necessary infrastructure and provide training to their staff to ensure a successful implementation of electronic taxation system. Again, it was recommended that tax authorities should continue to promote the use of electronic taxation systems to encourage voluntary compliance. Finally, it was recommended that tax authorities should focus on improving their electronic tax systems to make them more efficient and effective in order to consolidate on the gains already made in adoption of electronic taxation system.